2016
DOI: 10.1371/journal.pone.0161659
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Components of the Neurospora crassa pH Signaling Pathway and Their Regulation by pH and the PAC-3 Transcription Factor

Abstract: Environmental pH induces a stress response triggering a signaling pathway whose components have been identified and characterized in several fungi. Neurospora crassa shares all six components of the Aspergillus nidulans pH signaling pathway, and we investigate here their regulation during an alkaline pH stress response. We show that the N. crassa pal mutant strains, with the exception of Δpal-9, which is the A. nidulans palI homolog, exhibit low conidiation and are unable to grow at alkaline pH. Moreover, they… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 62 publications
3
11
0
Order By: Relevance
“…The results are presented in Fig 5. As can be observed, all studied genes showed potential motifs for PAC-3 binding [18]. The cellulase genes cbh-1 and gh7-1 contained three potential sites, while the gh3-2 glucosidase-encoding gene contained only two sites.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results are presented in Fig 5. As can be observed, all studied genes showed potential motifs for PAC-3 binding [18]. The cellulase genes cbh-1 and gh7-1 contained three potential sites, while the gh3-2 glucosidase-encoding gene contained only two sites.…”
Section: Resultsmentioning
confidence: 99%
“…At alkaline pH, PAC-3 is activated by PalB-catalyzed proteolysis, and active PAC-3 binds to the DNA of its target genes through the core consensus 5ʹ-BGCCVAGV-3ʹ in N . crassa [18]. …”
Section: Introductionmentioning
confidence: 99%
“…3). The comparison between MmImpα/PAC-3 NLS and NcImpα/PAC-3 NLS 52 calorimetric assays reveals that their K d values are the same considering the experimental error.…”
Section: Calorimetric Assays For the Binding Of Nit-2 And Pac-3 Nlss mentioning
confidence: 86%
“…PAC-3 is a transcription factor that is translocated to the nucleus at alkaline pH stress in N. crassa 52 . Calorimetric assays with the putative PAC-3 NLS and NcImpα demonstrated that this NLS peptide has a strong affinity (0.39 µM, Table 2) to NcImpα with a stoichiometry of 1:1 52 .…”
Section: What Is the Role Of Pac-3 Nls In Pac-3 Protein Transport?mentioning
confidence: 99%
See 1 more Smart Citation